Folk Concept of ‘A Person’: Structure and Warrant - Berniūnas, Renatas (Problemos, 2012)
The main goal of this paper is to discuss the folk concept of ‘a person’. The secondary goal is to present a new field of experimental philosophy by using its theoretical framework to study folk concepts. The major part of this paper is devoted to descriptive issues of the concept of a person: in one section I outline the very notion of folk conceptions and then discuss the folk concept of a person; in another section I present a cognitive scientific view of persons. Finally, I outline a tentative answer to the substantive question about the reliability of folk concepts. It is argued that this kind of empirical conceptual analysis (of ‘a person’ or any other concept) can be of use within the standard methodological tool-kit of analytic philosophy, it can contribute to conceptual clarity in cognitive science, and possibly shed some light on normative issues.